2018
DOI: 10.1002/cyto.a.23653
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Quantitative Evaluation of Human Leukocyte Interaction with Aspergillus fumigatus Conidia by Flow Cytometry

Abstract: Systemic infections with the opportunistic mold Aspergillus fumigatus are a great threat to immunocompromised patients such as transplant recipients. Immunological research on A. fumigatus involves the measurement of phagocytosis of fungal conidia (spores) by human phagocytes. Here, we present a fast and flexible way to analyze phagocytosis by flow cytometry using fluorescein isothiocyanate (FITC) labeling of conidia prior to co‐incubation with human leukocytes and an anti‐FITC counterstaining step postincubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…A mutant strain (pksP) lacking the DHN-melanin layer on the surface of conidia was phagocytosed more efficiently than the wild-type strain, in agreement with all the published data showing the protective role of DHN-melanin against immune cells (43). The observed phagocytosis rate was similar to primary neutrophils, which internalized around 40% of wild-type conidia after 2 h, reaching a maximum of 50% after 4 or 12 h (44,45). Measuring the release of inflammatory cytokines from dPLBs revealed that IL-8, but not IL-1β, increased over time following infection with opsonized conidia.…”
Section: Discussionsupporting
confidence: 88%
“…A mutant strain (pksP) lacking the DHN-melanin layer on the surface of conidia was phagocytosed more efficiently than the wild-type strain, in agreement with all the published data showing the protective role of DHN-melanin against immune cells (43). The observed phagocytosis rate was similar to primary neutrophils, which internalized around 40% of wild-type conidia after 2 h, reaching a maximum of 50% after 4 or 12 h (44,45). Measuring the release of inflammatory cytokines from dPLBs revealed that IL-8, but not IL-1β, increased over time following infection with opsonized conidia.…”
Section: Discussionsupporting
confidence: 88%
“…The lack of morphological characterization also results in unresolved spore clusters and the lack of properly identification of spores that are adherent to macrophages (Kraibooj et al, 2014). As a consequence, it is impossible to determine the precise phagocytosis measures solely based on cytometry data (Hartung et al, 2018). In contrast, microscopy-based methods provide comprehensive details about the phagocytosis process from both the host view and the pathogen view.…”
Section: Discussionmentioning
confidence: 99%
“…This method is very time-consuming since for each condition serial dilutions of lysed neutrophils are needed. Therefore, we and others have developed several approaches to determine phagocytosis of bacteria by neutrophils (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), many of them in multi-well plates. Here, we describe a powerful flow cytometry method to quantify phagocytosis of S. aureus by freshly isolated human neutrophils in vitro.…”
Section: Introductionmentioning
confidence: 99%